Platelet-Rich Plasma as a Pharmacopuncture Agent in Cervical Myofascial Pain - Nareswari, Irma; Kamal, Achmad Fauzi; Mihardja, Hasan; Yunus, Reyhan Eddy; Jusuf, Ahmad Aulia; Harahap, Alida Roswita; Wahyuni, Luh Karunia; Werdhani, Retno Asti; Handayani, Selfi; Rukmindar, Dion (Writing Center IMERI FMUI, 2025)
Chronic cervical myofascial pain (CMP) is a prevalent musculoskeletal disorder characterized by persistent neck pain, inflammation, functional impairment, and altered pain processing. Conventional treatments, including pharmacological therapy and physical rehabilitation, often provide limited and temporary relief. Increasing evidence suggests that chronic CMP involves not only peripheral nociceptive input but also nociplastic pain mechanisms driven by sustained neuroimmune dysregulation and central sensitization. Pharmacopuncture, combining acupuncture point stimulation with localized injection of therapeutic agents, has evolved with the introduction of regenerative biologics such as platelet-rich plasma (PRP). PRP contains concentrated platelets and bioactive growth factors, including VEGF, PDGF, and TGF-β, which exert anti-inflammatory and tissue-reparative effects. Emerging data indicate that PRP pharmacopuncture may reduce pro-inflammatory cytokines (e.g., IL-1β and TNF-α), modulate regulated cell death pathways (e.g., apoptosis and pyroptosis), and promote the restoration of myofascial tissue homeostasis. These mechanisms may contribute to both peripheral tissue repair and attenuation of nociplastic pain processing. This narrative review synthesizes current clinical and experimental evidence on the biological mechanisms and therapeutic potential of PRP pharmacopuncture in chronic CMP. Available studies report meaningful improvements in pain intensity and functional outcomes compared with conventional acupuncture or pharmacotherapy alone. However, substantial methodological heterogeneity may arise from PRP preparation protocols, acupoint selection, and outcome measures, limiting the ability to draw definitive conclusions. High-quality randomized controlled trials incorporating standardized protocols and mechanistic biomarkers are required to establish PRP pharmacopuncture as an evidence-based integrative treatment for chronic CMP.